Effect of Dietary Omega‐3 Fatty Acids on Tumor‐Associated Macrophages and Prostate Cancer Progression. Issue 14 (24th June 2016) - Liang, Pei; Henning, Susanne M.; Schokrpur, Shiruyeh; Wu, Lily; Doan, Ngan; Said, Jonathan; Grogan, Tristan; Elashoff, David; Cohen, Pinchas; Aronson, William J.
Abstract : BACKGROUND: Preclinical and clinical studies suggest that a fish oil‐based diet may play a role in delaying the progression of prostate cancer through a number of different mechanisms involving inflammatory pathways. Given the importance of tumor‐associated macrophages (TAMs) in carcinogenesis, we hypothesized that a fish oil‐based diet will inhibit TAM infiltration and delay the growth of prostate cancer. METHODS: Androgen sensitive mouse prostate cancer (MycCaP) allograft tumors were grown in fully immunocompetent FVB mice fed a high‐ fat fish oil (omega‐3) or corn oil (omega‐6) diet. Gene expression of markers for immune cell populations, cytokines, chemokines, and signaling pathways were determined by real‐time PCR and western blot in tumor tissue. Cell proliferation and apoptosis in vitro were measured by MTS assay and flow cytometry. RESULTS: Tumor volumes were significantly smaller in mice in ω‐3 versus the ω‐6 group ( P  = 0.048). Gene expression of markers for M1 and M2 macrophages (F4/80, iNOS, ARG1), associated cytokines (IL‐6, TNF alpha, IL‐10), and the chemokine CCL‐2 were also lower in the omega‐3 group. Correlative in vitro studies were performed in M1 and M2 polarized macrophages and mirrored the in vivo findings. Dietary fish oil and in vitro omega‐3 fatty acid administration reduced protein expression of transcription factors in the nuclear factor kappa B pathway leading to a significant decrease in gene expression of downstream targets (Bcl‐2, BCL‐XL, XIAP, survivin) in MycCap cells. CONCLUSIONS: These findings underscore the potential of fish oil in modulating the clinical course of human prostate cancer through the immune system. Further preclinical and clinical studies are warranted evaluating fish oil‐based therapies for inhibiting the recruitment and function of M1 and M2 tumor infiltrating macrophages. Prostate 76:1293–1302, 2016 . © 2016 Wiley Periodicals, Inc.